Birthing Waters: An Anglican View of Baptismal Regeneration - Crawford, Esteban E. (Journal of Anglican studies, 2024)
In what sense do Anglicans believe in baptismal regeneration? This article contends that according to historic Anglicanism, baptism effectually regenerates those who faithfully receive it. While this is a disputed claim even among Anglicans, it is consistent with the formularies of the Church of England, and it largely represents a predominant position held by Anglicans across the centuries. Article XXVII of the Thirty-Nine Articles of Religion will serve as the primary point of reference for assessing the above question. The following study is organized in three sections that respectively address: (1) the sacramental efficacy of baptism; (2) the regenerative nature of baptism; and (3) the need for faith to accompany baptism. Each section examines diverse historical expressions relevant to these doctrines in light of their scriptural basis. A brief reflection on infant baptism concludes the paper.